THE CORRELATION BETWEEN GRAMMAR AND VOCABULARY MASTERY TOWARD SCIENTIFIC-WRITING ABILITY AMONG THE STUDENTS OF PEACE COURSE PARE KEDIRI - Bisri, Muhammad Syafiq (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 6 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
This study is aimed to find out how the students’ grammar mastery is, the students’ vocabulary mastery is, whether there is any simultaneous correlation and partially correlation among grammar and vocabulary mastery towards scientific-writing ability among BTP students of PEACE English Course Pare Kediri. The quantitative approach was used to design this research. This study was conducted at PEACE English Course Pare Kediri. The population was 115 students of BTP Students of PEACE English Course Pare Kediri and after calculated by using Sloven formula, the sample taken was 90 students. Test and documentation were used to gain the data. The data gotten was computed by partial and multiple regressions then analyzed by using SPSS version 16.0. to find descriptive, simultaneous, and partial correlation. The results of the study were students’ grammar mastery belonged to good, students’ vocabulary mastery very good, and scientific-writing ability belongs to good. Simultaneously, grammar and vocabulary mastery contributed 86.5% to scientific-writing ability. Partially, the correlation of grammar mastery and vocabulary mastery towards scientific-writing ability is 30.05% and 27.8%.